Effects of Air Pollution on the Health of Older Adults during Physical Activities: Mapping Review - D'Oliveira A.* (2023)
© 2023 by the authors.Atmospheric pollutants present environmental threats to health and have been investigated in different environments, such as highways, squares, parks, and gyms. These environments are frequented by older adults, who are considered fragile to the harmful impacts of pollution present in the air. The aim was to analyze the state of the art on the effects of air pollution on the health of older adults during physical activities (PAs) through a mapping review. The search was performed in PubMed, Web of Science, Scopus, and Cinahl databases until June 2022. Of the 10,109 studies initially identified, 58 met the inclusion criteria. The most investigated health outcome was cardiovascular disease, followed by respiratory outcomes. Particulate matter (PM2.5 and PM10), nitrogen dioxide (NO2), and ozone (O3) were the most investigated pollutants. Of the 75 health outcomes investigated, in 29, air pollution had harmful effects on the health of the older adults during the practice of PA, more frequently in cardiovascular diseases. In 25 outcomes, the beneficial effects of PA to the health of the older adults remained, despite exposure to high and low concentrations of pollutants, most often in terms of mental disorders. We conclude that poor air quality is a harmful factor for the health of older adults during the practice of PAs, more frequently in cardiovascular and respiratory diseases. On the other hand, for mental-health-related outcomes (depression and cognition), in most studies, the beneficial effects of PA in older adults were maintained, even after exposure to pollutants.